Exercise 1

\lim_{ x \rightarrow 0 } \frac { { e }^{ x } - { e }^{ -x } }{ \sin { x } }

The best Maths tutors available
Intasar
4.9
4.9 (36 reviews)
Intasar
£48
/h
Gift icon
1st lesson free!
Paolo
4.9
4.9 (28 reviews)
Paolo
£30
/h
Gift icon
1st lesson free!
Shane
4.9
4.9 (23 reviews)
Shane
£25
/h
Gift icon
1st lesson free!
Jamie
5
5 (16 reviews)
Jamie
£25
/h
Gift icon
1st lesson free!
Matthew
5
5 (17 reviews)
Matthew
£30
/h
Gift icon
1st lesson free!
Petar
4.9
4.9 (12 reviews)
Petar
£40
/h
Gift icon
1st lesson free!
Harinder
5
5 (14 reviews)
Harinder
£15
/h
Gift icon
1st lesson free!
Farooq
4.9
4.9 (17 reviews)
Farooq
£40
/h
Gift icon
1st lesson free!
Intasar
4.9
4.9 (36 reviews)
Intasar
£48
/h
Gift icon
1st lesson free!
Paolo
4.9
4.9 (28 reviews)
Paolo
£30
/h
Gift icon
1st lesson free!
Shane
4.9
4.9 (23 reviews)
Shane
£25
/h
Gift icon
1st lesson free!
Jamie
5
5 (16 reviews)
Jamie
£25
/h
Gift icon
1st lesson free!
Matthew
5
5 (17 reviews)
Matthew
£30
/h
Gift icon
1st lesson free!
Petar
4.9
4.9 (12 reviews)
Petar
£40
/h
Gift icon
1st lesson free!
Harinder
5
5 (14 reviews)
Harinder
£15
/h
Gift icon
1st lesson free!
Farooq
4.9
4.9 (17 reviews)
Farooq
£40
/h
Gift icon
1st lesson free!
Let's go

Exercise 2

\lim_{ x \rightarrow { \infty }^{ + } } \frac { x }{ { (\ln { x }) }^{ 3 } + 2x }

Exercise 3

\lim_{ x \rightarrow 0 } ( \frac { 1 }{ x } - \frac { 1 }{ \sin { x } } )

Exercise 4

\lim_{ x \rightarrow \frac { \pi }{ 4 } } ( \tan { x } - 1) \sec { 2x }

Exercise 5

\lim_{ x \rightarrow 0 } { x }^{ \tan { x } }

Exercise 6

\lim_{ x \rightarrow 0 } { (\cot { x }) }^{ \sin { x } }

Exercise 7

\lim_{ x \rightarrow 2 } { (\frac { x }{ 2 }) }^{ \frac { 1 }{ x - 2 }}

Exercise 8

\lim_{ x \rightarrow 1 } \frac { \ln { x } }{ x - 1 }

Exercise 9

\lim_{ x \rightarrow 0 } \frac { \sin { 3x } }{ x - \frac { 3 }{ 2 } \sin { 2x } }

Exercise 10

\lim_{ x \rightarrow 0 } ( \arcsin { x } . \cot { x })

Exercise 11

\lim_{ x \rightarrow 0 } [ \frac { 1 }{ 2 } \frac { \sin { x }}{ \tan { x }} { (1 + \tan { 2x }) }^{ \frac { 4 }{ x }}]

Exercise 12

\lim_{ x \rightarrow 0 } \frac { \ln { (1 + x) } - \sin { x } }{ x \sin { x } }

Exercise 13

\lim_{ x \rightarrow 0 } \frac { 1 + \sin { x } - { e }^{ x } }{ { (\arctan { x }) }^{ 2 } }

Exercise 14

\lim_{ x \rightarrow 0 } [ \frac { 1 }{ \ln { ( 1 + x) } } - \frac { 1 }{ x }]

Exercise 15

\lim_{ x \rightarrow 0 } { (\frac { 1 + \tan { x } }{ 1 + \sin { x } } ) }^{ \frac { 1 }{ \sin { x }} }

Exercise 16

\lim_{ x \rightarrow 0 } { x} ^{ \sin { x } }

 

 

Solution of exercise 1

\lim_{ x \rightarrow 0 } \frac { { e }^{ x } - { e }^{ -x } }{ \sin { x } }

\lim_{ x \rightarrow 0 } \frac { { e }^{ x } - { e }^{ -x } }{ \sin { x } } = \frac { 0 }{ 0 }

\lim_{ x \rightarrow 0 } \frac { { e }^{ x } - { e }^{ -x } }{ \sin { x } } = \lim_{ x \rightarrow 0 } \frac { { e }^{ x } + { e }^{ -x } }{ \cos { x } } = 2

 

Solution of exercise 2

\lim_{ x \rightarrow { \infty }^{ + } } \frac { x }{ { (\ln { x }) }^{ 3 } + 2x }

\lim_{ x \rightarrow { \infty }^{ + } } \frac { x }{ { (\ln { x }) }^{ 3 } + 2x } = \frac { \infty }{ \infty }

\lim_{ x \rightarrow { \infty }^{ + } } \frac { x }{ { (\ln { x }) }^{ 3 } + 2x } = \lim_{ x \rightarrow { \infty }^{ + } } \frac { 1 }{ 3 { (\ln { x }) }^{ 2 } . \frac { 1 }{ x } + 2 }

\lim_{ x \rightarrow { \infty }^{ + } } \frac { 3 { (\ln { x }) }^{ 2 } }{ x } = \frac { \infty }{ \infty }

\lim_{ x \rightarrow { \infty }^{ + } } \frac { 1 }{ 3 { (\ln { x }) }^{ 2 } . \frac { 1 }{ x } + 2 } = \frac { 1 }{ 2 }

 

Solution of exercise 3

\lim_{ x \rightarrow 0 } ( \frac { 1 }{ x } - \frac { 1 }{ \sin { x } } )

\lim_{ x \rightarrow 0 } ( \frac { 1 }{ x } - \frac { 1 }{ \sin { x } } ) = \infty - \infty

\lim_{ x \rightarrow 0 } ( \frac { 1 }{ x } - \frac { 1 }{ \sin { x } } ) = \lim_{ x \rightarrow 0 } \frac { \sin { x } - x }{ x . \sin { x } } = \frac { 0 }{ 0 }

\lim_{ x \rightarrow 0 } \frac { \sin { x } - x }{ x . \sin { x } } = \lim_{ x \rightarrow 0 } \frac { \cos { x } - 1 }{ \sin { x } + x . \cos { x } } = \frac { 0 }{ 0 }

\lim_{ x \rightarrow 0 } \frac { \cos { x } - 1 }{ \sin { x } + x . \cos { x } } = \lim_{ x \rightarrow 0 } \frac { - \sin { x } }{ \cos { x } + \cos { x } - x . \sin { x } } = 0

 

Solution of exercise 4

\lim_{ x \rightarrow \frac { \pi }{ 4 } } ( \tan { x } - 1) \sec { 2x }

\lim_{ x \rightarrow \frac { \pi }{ 4 } } ( \tan { x } - 1) \sec { 2x } = 0 . \infty

\lim_{ x \rightarrow \frac { \pi }{ 4 } } \frac { ( \tan { x } - 1) }{ \cos { 2x } } = \frac { 0 }{ 0 }

\lim_{ x \rightarrow \frac { \pi }{ 4 } } \frac { 1 + ( \tan^{ 2 }{ x }) }{ -2 \sin { 2x } } = -1

 

Solution of exercise 5

\lim_{ x \rightarrow 0 } { x }^{ \tan { x } }

A = { x }^{ \tan { x } } \qquad \ln { A } = \tan { x } \ln { x } \qquad A = { e }^{ \tan { x } . \ln { x } }

\lim_{ x \rightarrow 0 } { x }^{ \tan { x } } = \lim_{ x \rightarrow 0 } { e }^{ \tan { x } . \ln { x } } = { e }^{ \lim_{ x \rightarrow 0 } ( { e }^{ \tan { x } . \ln { x } } ) } = { e }^{ \lim_{ x \rightarrow 0 } \frac { \ln { x } }{ \cot { x } } } = { e }^{ \lim_{ x \rightarrow 0 } [( - \frac { \frac { 1 }{ x } }{ \csc^{ 2 }{ x } }) }

= { e }^{ \lim_{ x \rightarrow 0 } \frac { - \sin^{ 2 }{ x } }{ x } } = { e }^{ \lim_{ x \rightarrow 0 } (-2 \sin{ x } . \cos { x } ) } = { e }^{ 0 } = 1

 

Solution of exercise 6

\lim_{ x \rightarrow 0 } { (\cot { x }) }^{ \sin { x } }

A = { (\cot { x }) }^{ \sin { x } } . \ln { A } = \sin { x } . \ln { (\cot { x }) }

A = { e }^{ \sin { x } \ln { (\cot { x } ) }}

\lim_{ x \rightarrow 0 } { (\cot { x }) }^{ \sin { x } } = \lim_{ x \rightarrow 0 } { e }^{ \sin { x } \ln { (\cot { x } ) }} = { e }^{ \lim_{ x \rightarrow 0 } \frac { \ln { (\cot { x } ) } }{ \csc { x } }

{ e }^{ \lim_{ x \rightarrow 0 } \frac { \frac { - \cosec^{ 2 }{ x } }{ \cot { x } } }{ \frac { - \cos { x } }{ \sin^{ 2 }{ x } } } } = { e }^{ \lim_{ x \rightarrow 0 } \frac { \cosec^{ 2 }{ x } \sin^{ 2 }{ x } }{ \cos { x } \cot { x }} } = { e }^{ \lim_{ x \rightarrow 0 } \frac { 1 }{ \cos { x } \frac { \cos { x } }{ \sin { x } }} } = { e }^{ \lim_{ x \rightarrow0 } \frac { \sin { x } }{ \cos^{ 2 }{ x } } } = { e }^{ 0 } = 1

 

Solution of exercise 7

\lim_{ x \rightarrow 2 } { (\frac { x }{ 2 }) }^{ \frac { 1 }{ x - 2 }}

\lim_{ x \rightarrow 2 } { ( \frac { x }{ 2 }) }^{ \frac { 1 }{ x - 2 } } = { 1 }^{ \infty } \qquad A = { (\frac { x }{ 2 } ) }^{ \frac { 1 }{ x - 2 } }

\ln { A } = \frac { 1 }{ x - 2 } \ln { ( \frac { x }{ 2 } ) } \qquad A = { e }^{ \frac { 1 }{ x - 2 } \ln { ( \frac { x }{ 2 }) } }

\lim_{ x \rightarrow 2 } { (\frac { x }{ 2 }) }^{ \frac { 1 }{ x - 2 } } = { e }^{ \lim_{ x \rightarrow 2 } [\frac { 1 }{ x - 2 } \ln { (\frac { x }{ 2 }) } ]} = { e }^{ \lim_{ x \rightarrow 2 } [ \frac { \ln { ( \frac { x }{ 2 } ) } }{ x - 2 } ]}

{ e }^{ \lim_{ x \rightarrow 2 } \frac { \frac { 1 }{ 2 } }{ \frac { x }{ 2 } } } = { e }^{ \frac { 1 }{ 2 } } = \sqrt { e }

 

Solution of exercise 8

\lim_{ x \rightarrow 1 } \frac { \ln { x } }{ x - 1 }

\lim_{ x \rightarrow 1 } \frac { \ln { x } }{ x - 1 } = \frac { 0 }{ 0 }

\lim_{ x \rightarrow 1 } \frac { \ln { x } }{ x - 1 } = \lim_{ x \rightarrow 1 } \frac { 1 }{ x } = 1

 

Solution of exercise 9

\lim_{ x \rightarrow 0 } \frac { \sin { 3x } }{ x - \frac { 3 }{ 2 } \sin { 2x } }

\lim_{ x \rightarrow 0 } \frac { \sin { 3x } }{ x - \frac { 3 }{ 2 } \sin { 2x } } = \frac { 0 }{ 0 }

\lim_{ x \rightarrow 0 } \frac { \sin { 3x } }{ x - \frac { 3 }{ 2 } \sin { 2x } } = \lim_{ x \rightarrow 0 } \frac { 3 \cos { 3x } }{ 1 - 3 \cos { 2x } } = - \frac { 3 }{ 2 }

 

Solution of exercise 10

\lim_{ x \rightarrow 0 } ( \arcsin { x } . \cot { x })

\lim_{ x \rightarrow 0 } ( \arcsin { x } . \cot { x }) = 0 . \infty

\lim_{ x \rightarrow 0 } ( \arcsin { x } . \cot { x }) = \lim_{ x \rightarrow 0 } \frac { \cos { x } \arcsin { x } }{ \sin { x } } =

= \lim_{ x \rightarrow 0 } \frac { - \sin { x } \arcsin { x } + \frac { \cos { x } }{ \sqrt { 1 - { x }^{ 2 } } } }{ \cos { x } } = 1

 

Solution of exercise 11

\lim_{ x \rightarrow 0 } [ \frac { 1 }{ 2 } \frac { \sin { x }}{ \tan { x }} { (1 + \tan { 2x }) }^{ \frac { 4 }{ x }}]

\lim_{ x \rightarrow 0 } [ \frac { 1 }{ 2 } \frac { \sin { x }}{ \tan { x }} { (1 + \tan { 2x }) }^{ \frac { 4 }{ x }}] = \frac { 1 }{ 2 } \lim_{ x \rightarrow 0 } (\cos { x }) \lim_{ x \rightarrow 0 } { (1 + \tan { 2x }) }^{ \frac { 4 }{ x } } =

\frac { 1 }{ 2 } \lim_{ x \rightarrow 0 } { (1 + \tan { 2x } ) }^{ \frac { 4 }{ x } } = { 1 }^{ \infty }

A = { (1 + \tan { 2x } }^{ \frac { 4 }{ x } } \qquad \ln { A } = \frac { 4 }{ x } \ln { (1 + \tan { 2x }) } \qquad A = { e }^{ \frac { 4 }{ x } \ln { (1 + \tan { 2x } ) } }

\frac { 1 }{ 2 } \lim_{ x \rightarrow 0 } { (1 + \tan { 2x } ) }^{ \frac { 4 }{ x } } = \frac { 1 }{ 2 } { e }^{ \lim_{ x \rightarrow 0 } \frac { 4 \ln {(1 + \tan { 2x })} }{ x } } = \frac { 1 }{ 2 } { e }^{ \lim_{ x \rightarrow 0 } \frac { 4 . 2 (1 + \tan^{ 2 }{ 2x }) }{ \ln { (1 + \tan { 2x } ) } } } = \frac { 1 }{ 2 } { e }^{ 8 }

 

Solution of exercise 12

\lim_{ x \rightarrow 0 } \frac { \ln { (1 + x) } - \sin { x } }{ x \sin { x } }

\lim_{ x \rightarrow 0 } \frac { \ln { (1 + x) } - \sin { x } }{ x \sin { x } } = \frac { 0 }{ 0 }

\lim_{ x \rightarrow 0 } \frac { \ln { (1 + x) } - \sin { x } }{ x \sin { x } } = \lim_{ x \rightarrow 0 } \frac { \frac { 1 }{ 1 + x } - \cos { x } }{ \sin { x } + x \cos { x } }=

= \lim_{ x \rightarrow 0 } \frac { - \frac { 1 }{ { (1 + x) }^{ 2 } } + \sin { x } }{ \cos { x } + \cos { x } - x \sin { x } } = - \frac { 1 }{ 2 }

 

Solution of exercise 13

\lim_{ x \rightarrow 0 } \frac { 1 + \sin { x } - { e }^{ x } }{ { (\arctan { x }) }^{ 2 } }

\lim_{ x \rightarrow 0 } \frac { 1 + \sin { x } - { e }^{ x } }{ { (\arctan { x }) }^{ 2 } } = \frac { 0 }{ 0 }

\lim_{ x \rightarrow 0 } \frac { 1 + \sin { x } - { e }^{ x } }{ { (\arctan { x }) }^{ 2 } } = \lim_{ x \rightarrow 0 } \frac { \cos { x } - { e }^{ x } }{ \frac { 2 \arctan { x } }{ 1 + { x }^{ 2 } } }

\lim_{ x \rightarrow 0 } \frac { \sin { x } - { e }^{ x } }{ \frac { 2 - 4x \arctan { x } }{ { (1 + { x }^{ 2 } ) }^{ 2 } } } = -\frac { 1 }{ 2 }

 

Solution of exercise 14

\lim_{ x \rightarrow 0 } [ \frac { 1 }{ \ln { ( 1 + x) } } - \frac { 1 }{ x }]

\lim_{ x \rightarrow 0 } [ \frac { 1 }{ \ln { ( 1 + x) } } - \frac { 1 }{ x }] = \infty - \infty

\lim_{ x \rightarrow 0 } [ \frac { 1 }{ \ln { ( 1 + x) } } - \frac { 1 }{ x }] = \lim_{ x \rightarrow 0 } \frac { x - \ln { (1 + x) } }{ x \ln { (1 + x ) } } = \frac { 0 }{ 0 }

\lim_{ x \rightarrow 0 } \frac { x - \ln { (1 + x) } }{ x \ln { (1 + x ) } } =  \lim_{ x \rightarrow 0 } \frac { 1 - \frac { 1 }{ 1 + x } }{ \ln { (1 + x) + \frac { x }{ 1 + x } }} =

\lim_{ x \rightarrow 0 } \frac { \frac { 1 + x - 1 }{ 1 + x } }{ \frac { (1 + x) \ln { (1 + x) x }}{ 1 + x } } = \lim_{ x \rightarrow 0 } \frac { x }{ \ln { (1 + x) } + x \ln { (1 + x) } + x }

\lim_{ x \rightarrow 0 } \frac { 1 }{ \frac { 1 }{ 1 + x } + \ln { (1 + x) } + \frac { x }{ 1 + x } + 1 } = \frac { 1 }{ 2 }

 

Solution of exercise 15

\lim_{ x \rightarrow 0 } { (\frac { 1 + \tan { x } }{ 1 + \sin { x } } ) }^{ \frac { 1 }{ \sin { x }} }

\lim_{ x \rightarrow 0 } { (\frac { 1 + \tan { x } }{ 1 + \sin { x } }) }^{ \frac { 1 }{ \sin { x } } } = { 1 }^{ \infty }

A = { (\frac { 1 + \tan { x } }{ 1 + \sin { x } } ) }^{ \frac { 1 }{ \sin { x }} } \qquad \ln { A } = \frac { 1 }{ \sin { x } } \ln { (\frac { 1 + \tan { x } }{ 1 + \sin { x } }) }

\ln { A } = \frac { 1 }{ \sin { x } } [ \ln { (1 + \tan { x } ) - \ln { (1 + \sin { x } ) } }]

\ln { A } = \frac { \ln { (1 + \tan { x } ) } - \ln { (1 + \sin { x } ) } }{ \sin { x } }

A = { e }^{ \frac { \ln { (1 + \tan { x } ) } - \ln { (1 + \sin { x } ) } }{ \sin { x } } }

\lim_{ x \rightarrow 0 } { (\frac { 1 + \tan { x } }{ 1 + \sin { x } } ) }^{ \frac { 1 }{ \sin { x }} } = { e }^{ \frac { \ln { (1 + \tan { x } ) } - \ln { (1 + \sin { x } ) } }{ \sin { x } } }

{ e }^{ \frac { \frac { 1 + \tan^{ 2 }{ x } }{ 1 + \tan{ x } } - \frac { \cos { x } }{ 1 + \sin { x } } }{ \cos { x } } } = { e }^{ 0 } = 1

 

Solution of exercise 16

\lim_{ x \rightarrow 0 } { x } ^{ \sin { x } }

\lim_{ x \rightarrow 0 } { x } ^{ \sin { x } } = { 0 }^{ 0 }

A = { x }^{ \sin { x } } \qquad \ln { A } = \sin { x } \ln { x } \qquad A = { e }^{ \sin { x } \ln { x } }

\lim_{ x \rightarrow 0 } { x } ^{ \sin { x } } = { e }^{ \lim_{ x \rightarrow 0 } (\sin { x } \ln { x }) } = { e }^{ \lim_{ x \rightarrow 0 } \frac { \ln { x } }{ \frac { 1 }{ \sin { x } } } }  = { e }^{ \lim_{ x \rightarrow 0 } \frac { \frac { 1 }{ x } }{ \frac { - \cos { x } }{ \sin^{ 2 }{ x } } } }

{ e }^{ \lim_{ x \rightarrow 0 } \frac { - \sin^{ 2 }{ x } }{ x \cos { x } } } = { e }^{ \lim_{ x \rightarrow 0 } \frac { =2 \sin { x } \cos { x } }{ \cos { x } - x \sin { x } } } = { e }^{ 0 } = 1

 

>

The platform that connects tutors and students

Did you like this article? Rate it!

1 Star2 Stars3 Stars4 Stars5 Stars 4.00 (3 rating(s))
Loading...

Hamza

Hi! I am Hamza and I am from Pakistan. My hobbies are reading, writing and playing chess. Currently, I am a student enrolled in the Chemical Engineering Bachelor program.